Flexible Regulation of Positive and Negative Emotion Expression: Reexamining the Factor Structure of the Flexible Regulation of Emotional Expression Scale (FREE) Based on Emotion Valence - Yanhua Zhao; Ping Wang (Journal of Intelligence)
The Flexible Regulation of Emotional Expression (FREE) Scale assesses individuals’ ability to enhance and suppress their emotional expressions across different situations. This study investigates the optimal factor structure of the FREE and emphasizes the importance of distinguishing between the regulation abilities for positive and negative expressions. A sample of 607 undergraduates (Mage = 19.02, SD = 1.02, 72.2% female) from Mainland China completed the questionnaire survey. Confirmatory factor analyses tested eight competing models of the FREE structure. Results indicated that the second-order model, featuring two higher-order factors (expressive enhancement and suppression abilities), fit the data well. An alternative second-order model, with two different higher-order factors (positive and negative emotion expressive abilities) and the same four first-order factors, demonstrated an even better fit. Various types of expressive ability scores showed predictive validity regarding emotion regulation self-efficacy, mental health outcomes, and relationship stress. Regulation of emotional expression can be represented by either regulation type or emotion valence, with the latter providing more informative insights. Flexible regulation of positive and negative emotion expression predicted fewer symptoms of depression, anxiety, stress, and relationship stress beyond emotion regulation self-efficacy. These findings highlight the importance of considering emotional valence in understanding flexibility in expression regulation.